Suffer the Little Children to Come: The Legal Rights of Unaccompanied Alien Children under United States Federal Court Jurisprudence. (13th June 2019) - Braaten, Claire Nolasco; Braaten, Daniel
Abstract: This article analyses United States (US) federal court jurisprudence to determine the legal rights of unaccompanied alien children (UAC) in various stages of immigration enforcement proceedings. After briefly discussing statistics on UAC in the US, it explains the legal context of US laws governing unaccompanied minors. Through examining 40 cases decided by the 12 US Circuit Courts of Appeals and various federal district courts, the article specifies how these courts interpreted and expanded on the procedural legal rights of UAC upon apprehension by immigration officials, during placement or detention decisions of the Office of Refugee Resettlement (ORR), prior to voluntary departure, during asylum proceedings, when rearrested after release, and while released pending immigration proceedings. According to the US federal courts, the government must grant unaccompanied minors procedural due process if it denies their release to the custody of an available and willing legal custodian. Case law examining the rights of UAC prior to voluntary departure emphasizes the need to grant them the opportunity to consult with a responsible adult, including a lawyer from a free legal services list that should be provided to them. Federal courts have also tackled various procedural issues concerning asylum claims filed by UAC. These include the right of third parties to custody of the unaccompanied minor, the minority age at the time of the asylum application, and the right of UAC to request consent for a state juvenile court's jurisdiction prior to applying for Special Immigrant Juvenile status. In removal proceedings against UAC, federal courts have elaborated on the scope and meaning of the right to counsel and the right to a bond rehearing upon their rearrest because of allegations of gang membership. Finally, federal courts have also examined issues concerning the rights of UAC while detained in ORR facilities and while in US territory. These include the right of an unaccompanied alien child to terminate a pregnancy while in ORR custody and the right not to be subjected to physical and sexual abuse while placed in a detention facility.